The Importance of Bottom Friction on Thermal Structure During Freezing of Small Shallow Lakes in Qinghai‐Tibet Plateau - Mengxiao Wang; Lijuan Wen; Lauri Arvola; Victor Stepanenko; Dongsheng Su (Water Resources Research, 2025)
Abstract There are numerous seasonal ice‐covered lakes on the Qinghai‐Tibet Plateau (QTP), which significantly influence local climate and lake ecosystems through thermal processes. Two QTP lakes, Ngoring (NL) and BLH‐A (BL), have similar latitudes, altitudes and climatic conditions. However, observed water temperature when freezing is lower in NL (about 0.5°C) and higher in BL (about 4°C). According to the novel lake thermal classification method proposed by Yang et al. (2021, https://doi.org/10.1029/2020gl091374) (Yang's method), NL and BL should be classified as cryomictic and cryostratified, respectively. However, the results calculated using both the original and improved Yang's method classified both lakes as cryomictic. Clearly, Yang's method was applicable to NL but not suitable for BL. This was probably because the method only considered lake area, depth, and wind speed, but neglected energy dissipation caused by bottom friction. Additionally, the LAKE model was employed to investigate the bottom friction effect. Results indicated that the extent of bottom friction effect on the two lakes was different and jointly influenced by small surface area and shallow depth.